High-efficiency ultrathin terahertz geometric metasurface for full-space wavefront manipulation at two frequencies. (8th January 2021) - Fan, Junpeng; Cheng, Yongzhi; He, Bin
Abstract: It has been demonstrated that metasurfaces have the ability to manipulate the wavefront. However, most multifunctional metasurfaces reported to date only operate in either reflection or transmission mode. In this paper, a bilayer metasurface based on geometric phase is proposed to independently tailor the wavefronts of transmitted and reflected circularly polarized (CP) waves at two different terahertz frequencies. More specifically, the metasurface can transform the incident CP wave to its cross-polarization component with a high conversion coefficient of about 0.87 (0.92) after refraction (reflection) at 0.6 (1.67) THz. The full 2 π phase shift can be obtained independently by varying the geometrical parameters of the unit-cell structure at two different operation modes. As proofs of concept, anomalous refraction and reflection, dual-band full-space cylindrical focusing metalens and vortex beam generation with different modes are numerically demonstrated. Our work provides an effective method to integrate two or more different functionalities into a simple metasurface-based device, and the independent phase modulation characteristic of our proposed metasurface also shows infinite potential in wavefront control of full space.